Senior moment [videorecording (DVD)] - Serafini, Giorgio, 1962-; Shatner, William; Smart, Jean; Lloyd, Christopher, 1938-; McManus, Don; Bowden, Katrina, 1988-; Goff, Gina G.; Brungardt, Kurt; Momenee, Christopher (Screen Media Films, 2020)
After losing his license for drag racing around Palm Springs, a retired NASA test pilot is forced to take public transportation where he finds a second chance at love.